Implication Principles Of Carousel Brainstorming Strategy As An Effeciency Motivation For Improving Reading Comprehensionin Pandemic Era - Rizal, Syamsul; Susanto, Ferri (CV. Inara, 2021)
This research was Constitutional law program students IAIN of Bengkulu that they haveless motivated and learning reading comprehension is bored, only 120 minutes in a week to study English at Faculty. The purpose of this research explain whether using Carousel Brainstorming Strategy can improve students’ Reading comprehension IAIN Bengkulu especiallyConstitutional law program students IAIN of Bengkuluin Academic year 2019/2020. Therefore, this research by Descriptive Qualitative and quantitative dataThe subjects instruments of this research were 30 students, consisted of females 23 and 7 males. The instruments of this research were reading tests, students observation checklists andlecturer observation checklist and fiels notes, and interview. The result of students mean score in Pre-assessment and every meeting, there are improvement in pre-assessment ( 50,1), The first meeting (62,43), and The second meeting (75,33). This research shows that using Carousel Brainstorming Strategy has successfully improved the students reading comprehension, the improvement was influenced by the used of interesting material chosen and lecturer’s participation toward the students.